PD-L1/L2 protein levels rapidly increase on monocytes via trogocytosis from tumor cells in classical Hodgkin lymphoma - Kawashima, Masaharu; Carreras, Joaquim; Higuchi, Hiroshi; Kotaki, Ryutaro; Hoshina, Takahiro; Okuyama, Kazuki; Suzuki, Naoto; Kakizaki, Masatoshi; Miyatake, Yuji; Ando, Kiyoshi; Nakayama, Masafumi; Umezu, Shinjiro; et al. (Leukemia, 2020)
In classical Hodgkin lymphoma (cHL)—characterized by the presence of Hodgkin and Reed-Sternberg (HRS) cells—tumor-associated macrophages (TAMs) play a pivotal role in tumor formation. However, the significance of direct contact between HRS cells and TAMs has not been elucidated. HRS cells and TAMs are known to express PD-L1, which leads to PD-1 + CD4 + T cell exhaustion in cHL. Here, we found that PD-L1/L2 expression was elevated in monocytes co-cultured with HRS cells within 1 h, but not in monocytes cultured with supernatants of HRS cells. Immunofluorescence analysis of PD-L1/L2 revealed that their upregulation resulted in membrane transfer called “trogocytosis” from HRS cells to monocytes. PD-L1/L2 upregulation was not observed in monocytes co-cultured with PD-L1/L2-deficient HRS cells, validating the hypothesis that there is a direct transfer of PD-L1/L2 from HRS cells to monocytes. In the patients, both ligands (PD-L1/L2) were upregulated in TAMs in contact with HRS cells, but not in TAMs distant from HRS cells, suggesting that trogocytosis occurs in cHL patients. Taken together, trogocytosis may be one of the mechanisms that induces rapid upregulation of PD-L1/L2 in monocytes to evade antitumor immunity through the suppression of T cells as mediated by MHC antigen presentation.